ANALISIS PERLAKUAN AKUNTANSI DAN PELAPORAN PAJAK PERTAMBAHAN NILAI DALAM MENINGKATKAN AKUNTABILITAS PELAPORAN KEUANGAN PADA KSO WILIAM MEGA NUSATAMA - Diana Gustinya, SE., M.Ak.; Atikah Ningtyas (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2018)
The purpose of this study is to know the analysis of accounting treatment and reporting value added tax and know accounting taxes related value added tax for accountability internal financial report KSO William Mega Nusatama. This research method uses qualitative method which describes accounting process of value added tax in relation to KSO William Mega Nusatama financial report. The result of the research is the company has conducted the procedure of value added tax in accordance with the Law No.42 of 2009, but has not applied value added tax treatment so that internal financial statements of the company can be said not accountable. And the discussion that can be conveyed is the company keeps the receipt of the installment journal from the consumer and acknowledges the VAT output, keeps the journal and acknowledges the Selling Price as a sale, makes a correction journal on the details of the sales repayment, keeps the journal at the time the company makes a contract of cooperation agreement to the vendor and acknowledges the existence value add taxes entries, keeps the journal at the time the company pays the invoice for the contract to the vendor, makes a correction journal on the payment details of the contract and non contract vendor, compares the nominal amount between the vendor payment details and the sales repayment with the input and output recap, value added tax at the end of 2015.